Positive electrode material, positive electrode plate and secondary battery
By combining single-crystal nickel-cobalt lithium manganese oxide and polycrystalline nickel-cobalt lithium manganese oxide secondary particles in the positive electrode material and limiting their size relationship, the microcrack generation and dynamics of high-nickel ternary positive electrode material in the long cycle are solved. The problem of low performance achieves high energy density, thermal stability and excellent electrochemical performance.
Patent Information
- Application Number
- CN202411364377.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-27
- Publication Date
- 2025-02-11
AI Technical Summary
The existing high-nickel ternary cathode materials are difficult to effectively suppress the occurrence of microcracks during long cycles, resulting in rapid attenuation of capacity. At the same time, the kinetic performance of single-crystal granular materials is low and the lithium deintercalation efficiency is not high.
The composite positive electrode material is used for the secondary particles of single-crystal nickel-cobalt lithium manganate and polycrystalt nickel-cobalt lithium manganate, and the size relationship range of the two is limited to ensure that the degree of particle breakage is small and the probability of side reaction is low during the cycle process. , and has high energy density and thermal stability.
The long cycle performance at high temperatures is excellent, the cycle stability and safety are improved, the transition metal elements migrate to the negative electrode sheet is low, the capacity retention rate is high, and the electrochemical performance is excellent.
Smart Images

Figure BDA0005066461480000151 
Figure BDA0005066461480000171
Abstract
Description
Technical Field
[0001] The present application relates to the field of battery technology, and in particular to a positive electrode material, a positive electrode sheet and a secondary battery. Background Art
[0002] Ternary cathode materials Li[Ni 1-x-y Co x (Mn or Al) y The energy density of O2 increases with the increase of its nickel content, so high-nickel ternary positive electrode materials are popular positive electrode materials for lithium-ion secondary batteries in the existing power energy field.
[0003] High-nickel ternary positive electrode materials can be divided into single crystal granular materials and polycrystalline granular materials. Among them, polycrystalline granular materials have the function of elongating and refining the size of the primary particles of the positive electrode material, so that the overall positive electrode material can improve the uniformity of volume change during charge and discharge, thereby effectively dispersing the forces applied in the process and reducing the probability of microcracks in the positive electrode material; even if microcracks are formed, the connection and tortuous grain boundaries of the polycrystalline granular materials will hinder their extension to the surface of the external secondary particles, so that the performance of the positive electrode material will not change significantly in the short term. However, it is still difficult for polycrystalline granular materials to effectively inhibit the generation of microcracks during long cycles, and once they break, they are prone to side reactions with the infiltrated electrolyte, which leads to rapid decay of the capacity of the positive electrode material. On the other hand, single crystal granular materials have no grain boundaries, no microcracks, and their specific surface area is much smaller than that of polycrystalline granular materials, so the probability of reaction with the electrolyte is lower and the stability is high, but the kinetic performance of this granular material is low, and the efficiency of lithium intercalation and deintercalation in the process of charge and discharge is low, which leads to low lithium intercalation efficiency and intercalation capacity of the overall positive electrode material. Summary of the invention
[0004] The purpose of the present application is to overcome the shortcomings of the prior art and provide a positive electrode material, which comprises single-crystal lithium nickel cobalt manganese oxide and polycrystalline lithium nickel cobalt manganese oxide secondary particles, and at the same time limits the size relationship range of the two so that the two materials can achieve a balanced combination. The material has a small degree of particle breakage during the cycle and a low probability of side reactions with the electrolyte. It also has a high energy density and thermal stability, and excellent long cycle performance at high temperatures.
[0005] To achieve the above-mentioned object, in a first aspect of the present application, the present application provides a positive electrode material, including single crystal nickel cobalt lithium manganese oxide particles and polycrystalline nickel cobalt lithium manganese oxide secondary particles;
[0006] The positive electrode material satisfies: 90≤(D1 / D2)×(D1 / D3)≤460;
[0007] Wherein, D1μm is the average particle size of polycrystalline lithium nickel cobalt manganese oxide secondary particles;
[0008] The D2μm is the average particle size of single crystal lithium nickel cobalt manganese oxide particles;
[0009] The D3 μm is the average particle size of the polycrystalline lithium nickel cobalt manganese oxide primary particles.
[0010] As an embodiment of the present application, the polycrystalline lithium nickel cobalt manganese oxide secondary particle chemical formula includes Li d Ni a Co b Mn c M y O2, wherein M includes at least one of Zr, Sr, Ta, Sb, Y, Nb, Mo and W, wherein 0.85<a<0.95, 0<b<1, a+b<1 and 0.95≤d≤1.1, 0≤y≤0.1.
[0011] As an embodiment of the present application, the chemical formula of the single crystal lithium nickel cobalt manganese oxide particle includes Li d′ Ni a′ Co b′ Mn c′ M′ y′ O2, wherein M′ includes at least one of Zr, Al, Mg, K, Na, Zn, Ge and Ba, wherein 0.87<a′<0.96, 0<b′<1, a′+b′<1 and 0.95≤d′≤1.1, 0≤y′≤0.1.
[0012] As an embodiment of the present application, the positive electrode material satisfies: 8 μm ≤ D1 μm ≤ 16 μm.
[0013] As an embodiment of the present application, the positive electrode material satisfies: 3 μm ≤ D2 μm ≤ 6 μm.
[0014] As an embodiment of the present application, the positive electrode material satisfies: 0.1 μm≤D3 μm≤0.3 μm.
[0015] As an embodiment of the present application, the positive electrode material satisfies: a≤a′.
[0016] As an embodiment of the present application, the particle size distribution curve of the positive electrode material is a bimodal structure curve, the particle size distribution curve includes a first curve peak and a second curve peak, and the peak value of the first curve peak is lower than the peak value of the second curve peak;
[0017] The particle size distribution curve satisfies: 15≤f / e≤95;
[0018] The e is the percentage of the area of the first curve peak to the total area of the particle size distribution curve, and the f is the percentage of the area of the second curve peak to the total area of the particle size distribution curve.
[0019] As an embodiment of the present application, at least part of the surface of the single crystal lithium nickel cobalt manganese oxide particles and the polycrystalline lithium nickel cobalt manganese oxide secondary particles is also provided with a shell layer;
[0020] The shell layer comprises an oxide of element X, wherein X comprises at least one of Mg, Zn, Al, Ce, Ti, Zr, B, and W.
[0021] As an embodiment of the present application, the mass content of the element X in the positive electrode material is 0.02-1%.
[0022] In a second aspect of the present application, the technical solution of the present application provides a secondary battery, including a positive electrode sheet, a negative electrode sheet and an electrolyte, wherein the positive electrode sheet includes the positive electrode material described in the present application, and the electrolyte includes a fluorine-containing additive;
[0023] The secondary battery satisfies: 12≤g*h / Dv 50 ≤225;
[0024] Among them, the Dv 50 μm is the particle size when the cumulative volume reaches 50% in the volume distribution of the positive electrode material;
[0025] The h% is the mass content of the fluorine-containing additive in the electrolyte;
[0026] The g ppm is the concentration of the transition metal element in the negative electrode plate after the secondary battery is charged and discharged for 600 times. The temperature of the charge and discharge cycle is 45° C., the charge and discharge rate is 1C / 1C, and the charge and discharge cut-off voltage is 2.8V to 4.25V.
[0027] As an embodiment of the present application, the secondary battery satisfies: 6 μm ≤ Dv 50 μm≤15μm.
[0028] As an embodiment of the present application, the secondary battery satisfies: 0.1%≤h%≤3%.
[0029] As an embodiment of the present application, the secondary battery satisfies: 150 ppm≤g ppm≤1500 ppm.
[0030] In a third aspect of the present application, the present application provides an electrical device, comprising the secondary battery, wherein the secondary battery serves as a power supply for the electrical device.
[0031] The beneficial effects of this application are:
[0032] The present application provides a positive electrode material, which includes single-crystal nickel cobalt lithium manganese oxide and polycrystalline nickel cobalt lithium manganese oxide secondary particles, and at the same time limits the size relationship range of the two materials so that the two materials can achieve a balanced combination. The material has a small degree of particle breakage during the cycle process and a low probability of side reactions with the electrolyte. It also has a high energy density and thermal stability, and excellent long-cycle performance at high temperatures. DETAILED DESCRIPTION
[0033] In order to make the purpose, technical solutions and advantages of the embodiments of the present application clearer, the technical solutions in the embodiments of the present application are described clearly and completely below. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present application.
[0034] In the present application, the technical features described in an open manner include closed technical solutions composed of the listed features, and also include open technical solutions containing the listed features.
[0035] In this application, when it comes to numerical ranges, unless otherwise specified, the above numerical ranges are deemed to be continuous and include the minimum and maximum values of the range, as well as each value between such minimum and maximum values. Further, when a range refers to an integer, each integer between the minimum and maximum values of the range is included. In addition, when multiple ranges are provided to describe features or characteristics, the ranges can be merged. In other words, unless otherwise specified, all ranges disclosed herein should be understood to include any and all subranges included therein.
[0036] The present application is further described below with specific embodiments:
[0037] The embodiment of the present application provides a positive electrode material, including single-crystal nickel cobalt lithium manganese oxide particles and polycrystalline nickel cobalt lithium manganese oxide secondary particles; the polycrystalline nickel cobalt lithium manganese oxide secondary particles are formed by agglomerating polycrystalline nickel cobalt lithium manganese oxide primary particles;
[0038] The positive electrode material satisfies: 90≤(D1 / D2)×(D1 / D3)≤460;
[0039] Wherein, D1μm is the average particle size of polycrystalline lithium nickel cobalt manganese oxide secondary particles;
[0040] The D2μm is the average particle size of single crystal lithium nickel cobalt manganese oxide particles;
[0041] The D3 μm is the average particle size of the polycrystalline lithium nickel cobalt manganese oxide primary particles.
[0042] When nickel cobalt lithium manganese oxide is used as a positive electrode material, the role and characteristics of polycrystalline nickel cobalt lithium manganese oxide particles and single-crystal nickel cobalt lithium manganese oxide particles are different. Although polycrystalline nickel cobalt lithium manganese oxide particles have uniform force, high lithium deintercalation kinetics, and even if microcracks appear during the cycle, due to the obstacles of connection and grain boundaries, it is difficult to extend to the surface of secondary particles in a short period of time, and the overall stability is good, but in the long cycle process, the trend of microcracks is still difficult to prevent, and once it breaks, it will react with the electrolyte and cause the cycle capacity to drop rapidly. On the other hand, although single-crystal nickel cobalt lithium manganese oxide particles will not have microcracks, and have a small specific surface area, a low probability of reaction with the electrolyte, and good thermal stability, their kinetics are poor, and they cannot achieve a long ion diffusion path, which inhibits the efficiency of lithium deintercalation. In order to take into account the characteristics of the two materials, the two materials are compounded in the technical solution of the present application to construct a relationship between the sizes of the two materials, wherein D1 / D2 is the ratio of the average particle size of the polycrystalline nickel cobalt manganese oxide secondary particles to the single crystal nickel cobalt manganese oxide particles. The control ratio range of the two can ensure that the single crystal nickel cobalt manganese oxide particles are fully filled in the gaps between the polycrystalline nickel cobalt manganese oxide secondary particles, thereby improving the overall density of the positive electrode material; D1 / D3 is the ratio of the average particle size of the polycrystalline nickel cobalt manganese oxide secondary particles to the primary particles that constitute the secondary particles. Constructing the ratio of the two can take into account the dynamic performance and force stability during lithium deintercalation, thereby ensuring Better cycle performance; after the relationship between the two is established and maintained within a specific ratio range, the particle sizes of the two materials are very different, which not only ensures the dense filling effect of single-crystalline lithium nickel cobalt manganese oxide and polycrystalline lithium nickel cobalt manganese oxide secondary particles, but also makes the stress points more dispersed. It can provide support points to alleviate the rupture problem of polycrystalline lithium nickel cobalt manganese oxide particles under high compaction, and the probability of reaction with the electrolyte can also be maintained at a low level. At the same time, the large difference in particle size will not cause large differences in the overall material charge transfer impedance, solid-phase mass transfer coefficient, etc., and the depth of lithium deintercalation and extraction during charging and discharging will be significantly different, thereby affecting the cycle stability and safety.
[0043] In some embodiments, under the described construction, the unit molar amount of nickel element in the single-crystalline lithium nickel cobalt manganese oxide particles must be no less than the unit molar amount of nickel element in the polycrystalline lithium nickel cobalt manganese oxide secondary particles. This can avoid too large a difference in the gram capacity of the two materials, the single-crystalline particles and the polycrystalline particles, and can avoid the problem of too low energy density of the overall material after compounding.
[0044] In some embodiments, the positive electrode material satisfies: (D1 / D2)×(D1 / D3) can be a range value of one or any two of 90, 100, 110, 120, 130, 150, 180, 200, 220, 250, 280, 300, 320, 350, 380, 400, 420, 450, 460.
[0045] In some embodiments, the polycrystalline lithium nickel cobalt manganese oxide secondary particle chemical formula includes Li d Ni a Co b Mn c M y O2, wherein M includes at least one of Zr, Sr, Ta, Sb, Y, Nb, Mo, and W, wherein 0.85<a<0.95, 0<b<1, a+b<1, and 0.95≤d≤1.1, 0≤y≤0.1. This makes the positive electrode material have a higher capacity and better cycle performance.
[0046] In some embodiments, the single crystal lithium nickel cobalt manganese oxide particle chemical formula includes Li d′ Ni a′ Co b′ Mn c′ M′ y′ O2, the M' includes at least one of Zr, Al, Mg, K, Na, Zn, Ge, and Ba, wherein 0.87<a'<0.96, 0<b'<1, a'+b'<1 and 0.95≤d'≤1.1, 0≤y'≤0.1. This makes the positive electrode material have fewer grain boundaries, which is beneficial to improve energy density and cycle performance.
[0047] In some embodiments, the positive electrode material satisfies: 8 μm≤D1 μm≤16 μm.
[0048] Further preferably, the D1μm can be a range value of one or any two of 8μm, 8.5μm, 8.6μm, 8.8μm, 9μm, 9.5μm, 10μm, 10.5μm, 10.6μm, 11μm, 12μm, 13μm, 13.2μm, 13.5μm, 15μm, and 16μm.
[0049] In some embodiments, the positive electrode material satisfies: 3 μm≤D2 μm≤6 μm.
[0050] Further preferably, the D2μm may be a range value of one or any two of 3μm, 3.2μm, 3.3μm, 3.5μm, 3.6μm, 3.8μm, 4μm, 4.2μm, 4.5μm, 4.8μm, 4.9μm, 5μm, 5.5μm, and 6μm.
[0051] In some embodiments, the positive electrode material satisfies: 0.1 μm≤D3 μm≤0.3 μm.
[0052] Further preferably, the D3μm may be a range value of one or any two of 0.1μm, 0.12μm, 0.15μm, 0.18μm, 0.19μm, 0.2μm, 0.21μm, 0.25μm, 0.28μm, 0.3μm.
[0053] The average particle size of single-crystal nickel cobalt manganese oxide particles and the average particle size of polycrystalline nickel cobalt manganese oxide secondary particles not only affect the specific surface area of the overall positive electrode material, and thus the probability of side reactions with the electrolyte, but also affect the contact effect and mechanical bearing capacity between the particles. When single-crystal nickel cobalt manganese oxide particles and polycrystalline nickel cobalt manganese oxide secondary particles within the above range are selected, the comprehensive electrochemical performance of the resulting positive electrode material can be further improved.
[0054] In some embodiments, the testing method of D1, D2, and D3 of the positive electrode material is: observing the positive electrode material under a scanning electron microscope, screening single-crystalline nickel cobalt lithium manganese oxide particles and selecting at least 20 particle samples to measure the particle size using a scanning electron microscope measurement tool and calculate the average value, which is D2; screening polycrystalline nickel cobalt lithium manganese oxide secondary particles and selecting at least 20 particle samples to measure the particle size using a scanning electron microscope measurement tool and calculate the average value, which is D1; screening the primary particles in the polycrystalline nickel cobalt lithium manganese oxide secondary particles and selecting at least 20 primary particle samples to measure the particle size using a scanning electron microscope measurement tool and calculate the average value, which is D3.
[0055] In some embodiments, the particle size distribution curve of the positive electrode material is a bimodal structure curve, the particle size distribution curve includes a first curve peak and a second curve peak, the peak value of the first curve peak is lower than the peak value of the second curve peak; the particle size distribution curve satisfies: 15≤f / e≤95; e is the percentage value of the area of the first curve peak to the total area of the particle size distribution curve, and f is the percentage value of the area of the second curve peak to the total area of the particle size distribution curve.
[0056] Based on the particle size control and content ratio range of the single crystal nickel cobalt lithium manganese oxide particles and the polycrystalline nickel cobalt lithium manganese oxide secondary particles in the positive electrode material described in this application, the positive electrode material will have two main curve peaks in the distribution curve when performing overall particle size analysis, the distribution corresponds to two kinds of particles, and the peak intensity of the curve presents the above-mentioned specific ratio. For example, f / e can be a range value of one or any two of 2, 5, 8, 10, 12, and 15. When f / e is in the above range, the positive electrode material can have both high compaction ability and kinetic characteristics. The positive electrode material has a higher compaction ability, which can reduce the particle crushing phenomenon caused by the accumulation of lattice shrinkage and expansion stress during the cycle. Therefore, the battery composed of the positive electrode material has high energy density, long cycle life and excellent kinetic performance, which can meet the long endurance and fast charging requirements of the power battery.
[0057] In some embodiments, the single crystal lithium nickel cobalt manganese oxide and polycrystalline lithium nickel cobalt manganese oxide secondary particles are further provided with a shell layer on at least a portion of their surface;
[0058] The shell layer comprises an oxide of element X, wherein X comprises at least one of Mg, Zn, Al, Ce, Ti, Zr, B, and W.
[0059] In some embodiments, the mass content of the element X in the positive electrode material is 0.02-1%.
[0060] Further preferably, the mass content of the element X in the positive electrode material is in the range of one or any two of 0.02%, 0.05%, 0.08%, 0.1%, 0.2%, 0.3%, 0.5%, 0.6%, 0.8%, 1%.
[0061] In some embodiments, the mass content of element X in the positive electrode material is directly confirmed by using an EDS surface scanning mode of a scanning electron microscope.
[0062] Modification of lithium nickel cobalt manganese oxide with the above metal oxides can effectively improve its conductivity and stability, especially for the shell modification of the two different particles in the present application, it can improve the structural strength and interface stability of polycrystalline lithium nickel cobalt manganese oxide secondary particles, as well as the lithium deintercalation kinetics of single-crystalline lithium nickel cobalt manganese oxide particles. Under the above addition and modification ratio, the electrochemical performance of the obtained positive electrode material is further improved.
[0063] It should be noted that the single-crystal nickel cobalt manganese oxide particles and polycrystalline nickel cobalt manganese oxide secondary particles described in the technical solution of the present application can be prepared by conventional methods. For example, the polycrystalline nickel cobalt manganese oxide secondary particles are mixed with a nickel cobalt manganese hydroxide precursor and a lithium source, and then placed in a heating environment containing oxygen for heat treatment. The obtained sintered product is ground, crushed, and washed with water, and then an appropriate amount of lithium source is added and mixed. Then, a secondary heating treatment is performed in a heating environment containing oxygen, and sieved to obtain polycrystalline nickel cobalt manganese oxide secondary particles. When the lithium source is added, a precursor of element X, such as X oxide or an acid containing X, can be added at the same time for mixing, so as to construct a shell layer on the surface of the final product. The heating treatment temperature can be 700-750°C, and the secondary heating treatment temperature can be 300-350°C. For another example, the single-crystalline nickel cobalt lithium manganese oxide particles are mixed with a nickel cobalt manganese hydroxide precursor and a lithium source, and then placed in a heating environment containing oxygen for heat treatment. The obtained sintered product is crushed, and then further subjected to a secondary heat treatment in a heating environment containing oxygen, and sieved to obtain single-crystalline nickel cobalt lithium manganese oxide particles. Before adding the lithium source and before the secondary heat treatment, a precursor of element X, such as an oxide of X or an acid containing X, can be added and mixed to construct a shell layer on the surface of the final product. The temperature of the heat treatment can be 750-800°C, and the temperature during the secondary heat treatment can be 580-620°C.
[0064] The present application also provides a secondary battery, comprising a positive electrode sheet, a negative electrode sheet and an electrolyte, wherein the positive electrode sheet comprises the positive electrode material described in the present application, and the electrolyte comprises a fluorine-containing additive;
[0065] The secondary battery satisfies: 12≤g*h / Dv 50 ≤225;
[0066] Among them, the Dv 50 μm is the particle size when the cumulative volume reaches 50% in the volume distribution of the positive electrode material;
[0067] The h% is the mass content of the fluorine-containing additive in the electrolyte;
[0068] The g ppm is the concentration of the transition metal element in the negative electrode plate after the secondary battery is charged and discharged for 600 times. The temperature of the charge and discharge cycle is 45° C., the charge and discharge rate is 1C / 1C, and the charge and discharge cut-off voltage is 2.8V to 4.25V.
[0069] In addition to the problem of microcracks, lithium nickel cobalt manganese oxide, especially lithium nickel cobalt manganese oxide with high nickel composition, is very easy to react with the electrolyte, and the probability of mixing of nickel ions and lithium ions contained therein is also high, and the thermal stability is poor. For this reason, the technical solution of the present application is compounded with two particles of specific sizes, and the obtained positive electrode material has ideal thermal stability, side reaction inertness, density and lithium deintercalation activity. When applied to secondary batteries, the electrolyte prepared with fluorine-containing additives can further improve the stability of the positive electrode material, so that the integrity and dimensional stability of the positive electrode material are high, assist the stable formation of the SEI film and improve the performance of the secondary battery. After a long cycle, the secondary battery can be maintained within the above-mentioned relationship range, and a higher capacity retention rate and a lower DCR growth rate can be achieved under high temperature and long cycle conditions.
[0070] In some embodiments, the secondary battery satisfies: 6 μm ≤ Dv 50 μm≤15μm.
[0071] Further preferably, the Dv 50 μm is a range value of one or any two of 6μm, 7μm, 8μm, 9μm, 10μm, 11μm, 12μm, 13μm, 14μm, and 15μm. 50 When within the above range, the polycrystalline particles and single crystal particles in the positive electrode material can achieve a better grading effect, so that the positive electrode material system has a higher compaction ability and excellent dynamic performance. The high compaction ability can meet the high compaction density design of the positive electrode plate of the secondary battery, and improve the energy density of the secondary battery. In addition, it can also effectively improve the ability of the positive electrode material to resist particle breakage during a long cycle, thereby improving the cycle performance of the secondary battery. The dynamic performance can meet the fast charging requirements of the secondary battery.
[0072] The Dv 50 The test method is to use a laser particle size analyzer to test and confirm.
[0073] In some embodiments, the secondary battery satisfies: 0.1%≤h%≤3%.
[0074] Further preferably, the h% is a range value of one or any two of 0.1%, 0.5%, 1%, 1.2%, 1.5%, 1.8%, 2%, 2.2%, 2.5%, 2.8%, 3%. When h% is within the range, an interface film rich in LiF can be generated on the surface of the negative electrode, improving the stability of the interface film, thereby significantly improving the cycle stability of the secondary battery. At the same time, the content of the fluorine-containing additive within the above range also helps to improve the flame retardant properties of the electrolyte system, thereby achieving the effect of improving the thermal stability of the secondary battery. In some embodiments, the fluorine-containing additive includes at least one of fluoroethylene carbonate, difluorobis(oxalyl)phosphate lithium and tetrafluorooxalyl)phosphate lithium.
[0075] In some embodiments, the secondary battery satisfies: 150 ppm≤g ppm≤1500 ppm.
[0076] Further preferably, the g ppm is a range value of one or any two of 150ppm, 200ppm, 250ppm, 300ppm, 350ppm, 400ppm, 450ppm, 500ppm, 550ppm, 600ppm, 650ppm, 700ppm, 750ppm, 800ppm, 850ppm, 900ppm, 950ppm, 1000ppm, 1200ppm, and 1500ppm.
[0077] The present application provides an electrical device, comprising the secondary battery, wherein the secondary battery serves as a power supply for the electrical device.
[0078] The present invention is further described below with specific examples, which are not to be construed as limiting the scope of the present invention:
[0079] Example 1
[0080] A positive electrode material, the preparation method comprising the following steps:
[0081] (1) Preparation of polycrystalline lithium nickel cobalt manganese oxide secondary particles:
[0082] (1.1) The particle size Dv 50 = 9.8μm Ni 0.90 Co 0.05 Mn 0.05 (OH)2 particles are mixed with lithium source LiOH·H2O and ZrO2 to obtain a first mixture; the Li element in the lithium source is mixed with Ni 0.90 Co 0.05 Mn 0.05 The total molar ratio of Ni, Co and Mn elements in the (OH)2 particles is 1.06:1; the added concentration of ZrO2 is 2500ppm;
[0083] (1.2) introducing oxygen into the first mixture in an oxygen atmosphere furnace and heating the mixture at 715° C. for 12 h to obtain a first sintered product;
[0084] (1.3) The first sintered product is ground and crushed, then washed with water, and a proper amount of LiOH·H2O is added to the water and mixed, filtered and dried, and then H3BO3 is added and mixed evenly, oxygen is introduced into an oxygen atmosphere furnace and heated for a second time at 330°C for 10 hours to obtain a second sintered product; the added concentration of H3BO3 is 1500ppm;
[0085] (1.4) The second sintered product is screened to obtain Li 1.05 Ni 0.90 Co 0.05 Mn 0.045 Zr 0.05 O2 polycrystalline lithium nickel cobalt manganese oxide secondary particles.
[0086] (2) Preparation of single crystal lithium nickel cobalt manganese oxide particles:
[0087] (2.1) The particle size Dv 50 =3.3μmNi 0.92 Co 0.06 Mn 0.02 (OH)2 particles are mixed with lithium source LiOH·H2O and ZrO2 to obtain a first mixture; the Li element in the lithium source is mixed with Ni 0.92 Co 0.06 Mn 0.02 The total molar ratio of Ni, Co and Mn elements in the (OH)2 particles is 1.04:1; the added concentration of ZrO2 is 3000ppm;
[0088] (2.2) introducing oxygen into the first mixture in an oxygen atmosphere furnace and heating the mixture at 780° C. for 13 h to obtain a first sintered product;
[0089] (2.3) grinding and crushing the first sintered product, then adding Al2O3 and mixing evenly, introducing oxygen into an oxygen atmosphere furnace and performing a secondary heating treatment at 600°C for 10 hours to obtain a second sintered product; the added concentration of Al2O3 is 1000ppm;
[0090] (2.4) The second sintered product is screened to obtain Li 1.05 Ni 0.92 Co 0.06 Mn 0.014 Zr 0.06 O2 single crystal lithium nickel cobalt manganese oxide particles.
[0091] (3) Preparation of positive electrode materials:
[0092] Li 1.05 Ni 0.90 Co 0.05 Mn 0.045 Zr 0.05 O2 polycrystalline lithium nickel cobalt manganese oxide secondary particles and Li 1.05 Ni 0.92 Co 0.06 Mn 0.014 Zr 0.06 O2 single crystal nickel cobalt lithium manganese oxide particles are evenly mixed in a mass ratio of 7:3 to obtain the positive electrode material.
[0093] Example 2
[0094] A positive electrode material, the preparation method comprising the following steps:
[0095] (1) Preparation of polycrystalline lithium nickel cobalt manganese oxide secondary particles:
[0096] (1.1) The particle size Dv 50 =12.5μmNi 0.90 Co 0.05 Mn 0.05 (OH)2 particles are mixed with lithium source LiOH·H2O and ZrO2 to obtain a first mixture; the Li element in the lithium source is mixed with Ni 0.90 Co 0.05 Mn 0.05 The total molar ratio of Ni, Co and Mn elements in the (OH)2 particles is 1.06:1; the added concentration of ZrO2 is 2500ppm;
[0097] (1.2) introducing oxygen into the first mixture in an oxygen atmosphere furnace and heating the mixture at 725° C. for 12 h to obtain a first sintered product;
[0098] (1.3) The first sintered product is ground and crushed, then washed with water, and a proper amount of LiOH·H2O is added to the water and mixed, filtered and dried, and then H3BO3 is added and mixed evenly, oxygen is introduced into an oxygen atmosphere furnace and heated for a second time at 330°C for 10 hours to obtain a second sintered product; the added concentration of H3BO3 is 1500ppm;
[0099] (1.4) The second sintered product is screened to obtain Li 1.05 Ni 0.90 Co 0.05 Mn 0.045 Zr 0.05 O2 polycrystalline lithium nickel cobalt manganese oxide secondary particles.
[0100] (2) The preparation of single crystal lithium nickel cobalt manganese oxide particles is the same as in Example 1.
[0101] (3) The preparation of the positive electrode material is the same as in Example 1.
[0102] Example 3
[0103] A positive electrode material, the preparation method comprising the following steps:
[0104] (1) Preparation of polycrystalline lithium nickel cobalt manganese oxide secondary particles:
[0105] (1.1) The particle size Dv 50 =7.6μmNi 0.90 Co 0.05 Mn 0.05 (OH)2 particles are mixed with lithium source LiOH·H2O and ZrO2 to obtain a first mixture; the Li element in the lithium source is mixed with Ni 0.90 Co 0.05 Mn 0.05 The total molar ratio of Ni, Co and Mn elements in the (OH)2 particles is 1.06:1; the added concentration of ZrO2 is 2500ppm;
[0106] (1.2) introducing oxygen into the first mixture in an oxygen atmosphere furnace and heating the mixture at 735° C. for 12 h to obtain a first sintered product;
[0107] (1.3) The first sintered product is ground and crushed, then washed with water, and a proper amount of LiOH·H2O is added to the water and mixed, filtered and dried, and then H3BO3 is added and mixed evenly, oxygen is introduced into an oxygen atmosphere furnace and heated for a second time at 330°C for 10 hours to obtain a second sintered product; the added concentration of H3BO3 is 2000ppm;
[0108] (1.4) The second sintered product is screened to obtain Li 1.05 Ni 0.90 Co 0.05 Mn 0.045 Zr 0.05 O2 polycrystalline lithium nickel cobalt manganese oxide secondary particles.
[0109] (2) The preparation of single crystal lithium nickel cobalt manganese oxide particles is the same as in Example 1.
[0110] (3) The preparation of the positive electrode material is the same as in Example 1.
[0111] Example 4
[0112] A positive electrode material, the preparation method comprising the following steps:
[0113] (1) Preparation of polycrystalline lithium nickel cobalt manganese oxide secondary particles:
[0114] (1.1) The particle size Dv 50=15.2μmNi 0.90 Co 0.05 Mn 0.05 (OH)2 particles are mixed with lithium source LiOH·H2O and ZrO2 to obtain a first mixture; the Li element in the lithium source is mixed with Ni 0.90 Co 0.05 Mn 0.05 The total molar ratio of Ni, Co and Mn elements in the (OH)2 particles is 1.06:1; the added concentration of ZrO2 is 2500ppm;
[0115] (1.2) introducing oxygen into the first mixture in an oxygen atmosphere furnace and heating the mixture at 735° C. for 12 h to obtain a first sintered product;
[0116] (1.3) The first sintered product is ground and crushed, then washed with water, and a proper amount of LiOH·H2O is added to the water and mixed, filtered and dried, and then H3BO3 is added and mixed evenly, oxygen is introduced into an oxygen atmosphere furnace and heated for a second time at 330°C for 10 hours to obtain a second sintered product; the added concentration of H3BO3 is 1500ppm;
[0117] (1.4) The second sintered product is screened to obtain Li 1.05 Ni 0.90 Co 0.05 Mn 0.045 Zr 0.05 O2 polycrystalline lithium nickel cobalt manganese oxide secondary particles.
[0118] (2) Preparation of single crystal lithium nickel cobalt manganese oxide particles:
[0119] (2.1) The particle size Dv 50 =3.3μmNi 0.92 Co 0.06 Mn 0.02 (OH)2 particles are mixed with lithium source LiOH·H2O and ZrO2 to obtain a first mixture; the Li element in the lithium source is mixed with Ni 0.92 Co 0.06 Mn 0.02 The total molar ratio of Ni, Co and Mn elements in the (OH)2 particles is 1.04:1; the added concentration of ZrO2 is 3000ppm;
[0120] (2.2) introducing oxygen into the first mixture in an oxygen atmosphere furnace and heating the mixture at 790° C. for 14 h to obtain a first sintered product;
[0121] (2.3) grinding and crushing the first sintered product, then adding Al2O3 and mixing evenly, introducing oxygen into an oxygen atmosphere furnace and performing a secondary heating treatment at 600°C for 10 hours to obtain a second sintered product; the added concentration of Al2O3 is 1000ppm;
[0122] (2.4) The second sintered product is screened to obtain Li 1.05 Ni 0.92 Co 0.06 Mn 0.014 Al 0.06 O2 single crystal lithium nickel cobalt manganese oxide particles.
[0123] (3) The preparation of the positive electrode material is the same as in Example 1.
[0124] Embodiments 5 to 12
[0125] A positive electrode material, the preparation process is the same as that of Example 1, except that when preparing polycrystalline nickel cobalt lithium manganese oxide particles and / or preparing single crystal nickel cobalt lithium manganese oxide particles, the selected Ni 0.90 Co 0.05 Mn 0.05 (OH)2 particles, and / or Ni 0.92 Co 0.06 Mn 0.02 The particle sizes of (OH)2 particles are different, and positive electrode materials with different (D1 / D2)×(D1 / D3) are obtained. At the same time, in step (1.3), one of ZrO2 and WO3 is selected to replace H3BO3 so that the metal elements of the metal oxide in the shell layer on the surface of the prepared polycrystalline nickel cobalt lithium manganese oxide secondary particles are different, and / or in step (2.3), for example, MgO is selected to replace Al2O3 so that the metal elements and contents of the metal oxide in the shell layer on the surface of the prepared single crystal nickel cobalt lithium manganese oxide particles are different.
[0126] Example 13
[0127] A positive electrode material, the difference from Example 1 is that the polycrystalline nickel cobalt lithium manganese oxide secondary particles are prepared using a particle size Dv 50 =6μmNi 0.92 Co 0.6 Mn 0.2 (OH)2 particles. The single crystal nickel cobalt lithium manganese oxide particles are prepared using a particle size Dv 50 =3.3μmNi 0.94 Co 0.04 Mn 0.02 (OH)2 particles.
[0128] Embodiment 14
[0129] A positive electrode material, the difference from Example 1 is that the polycrystalline nickel cobalt lithium manganese oxide secondary particles are prepared using a particle size Dv 50 =6μmNi 0.94 Co 0.04 Mn 0.02 (OH)2 particles. The single crystal nickel cobalt lithium manganese oxide particles are prepared using a particle size Dv 50 =3.3μmNi 0.95 Co 0.03 Mn 0.02 (OH)2 particles.
[0130] Embodiment 15
[0131] A positive electrode material, which is different from Example 1 only in that the mass ratio of the polycrystalline nickel cobalt lithium manganese oxide secondary particles to the single crystal nickel cobalt lithium manganese oxide particles when mixed is 5:5.
[0132] Example 16
[0133] A positive electrode material, which is different from Example 1 only in that the mass ratio of the polycrystalline nickel cobalt lithium manganese oxide secondary particles to the single crystal nickel cobalt lithium manganese oxide particles when mixed is 8:2.
[0134] Embodiment 17
[0135] A positive electrode material, the difference from Example 1 is that when preparing the polycrystalline nickel cobalt lithium manganese oxide secondary particles, the ZrO2 is replaced by SrO with an equal added concentration, and when preparing the single crystal nickel cobalt lithium manganese oxide particles, the ZrO2 is replaced by MgO with an equal added concentration.
[0136] Comparative Example 1
[0137] A positive electrode material, the difference from Example 1 is that the polycrystalline nickel cobalt lithium manganese oxide secondary particles are prepared using a particle size Dv 50 =17μmNi 0.90 Co 0.05 Mn 0.05 (OH)2 particles.
[0138] Comparative Example 2
[0139] A positive electrode material, which differs from Example 1 only in that the positive electrode material contains only LiNi 0.90 Co 0.05 Mn 0.05 O2 polycrystalline lithium nickel cobalt manganese oxide secondary particles.
[0140] Comparative Example 3
[0141] A positive electrode material, which differs from Example 1 only in that the positive electrode material contains only LiNi0.90 Co 0.05 Mn 0.05 O2 single crystal lithium nickel cobalt manganese oxide particles.
[0142] Comparative Example 4
[0143] A positive electrode material, the difference from Example 1 is that the polycrystalline nickel cobalt lithium manganese oxide secondary particles are prepared using a particle size Dv 50 = 5μm Ni 0.90 Co 0.05 Mn 0.05 (OH)2 particles.
[0144] The parameters of the positive electrode materials obtained in various embodiments and comparative examples are shown in Table 1.
[0145] Where A = (D1 / D2) × (D1 / D3);
[0146] X is a metal element in the metal oxide contained in the shell layer of the positive electrode material;
[0147] Table 1
[0148]
[0149] The positive electrode materials of the above embodiments and comparative examples are used to prepare secondary batteries, and the preparation method is as follows:
[0150] (1) Preparation of positive electrode sheet: The positive electrode material obtained in each embodiment / comparative example is uniformly mixed with conductive carbon black and polyvinylidene fluoride in a high-speed vacuum mixer at a mass ratio of 97:2:1, and then N-methylpyrrolidone is added and stirred for 12 hours to prepare a slurry, which is then coated on an aluminum foil by a coating machine, dried at 110° C., rolled, cut into pieces, and slit to obtain a positive electrode sheet;
[0151] (2) Preparation of negative electrode sheet: Graphite, acetylene black, styrene-butadiene rubber and sodium carboxymethyl cellulose were uniformly mixed in a high-speed vacuum mixer at a mass ratio of 96:2:1:1, and then deionized water was added and stirred for 12 h to prepare a slurry, which was then coated on a copper foil by a coater, dried at 120° C., rolled, cut into pieces, and slit to obtain a negative electrode sheet;
[0152] (3) Preparation of secondary battery: The positive and negative electrode sheets and the separator are wound to obtain a bare battery cell, which is then placed in an outer packaging aluminum plastic film, dried, injected with electrolyte, and vacuum packaged to obtain the secondary battery. Wherein, a polyethylene polymer film is used as a separator, the electrolyte is an organic solution of ethylene carbonate and dimethyl carbonate mixed in a volume ratio of 1:1, 1 mol / L lithium hexafluorophosphate is used as a lithium salt, and fluoroethylene carbonate is added as an additive. The proportion of the additive in the electrolyte is h wt%, as shown in Table 2.
[0153] The prepared battery was subjected to the following performance tests:
[0154] (1) Low-rate discharge capacity test process: set the ambient temperature to 25°C, let the secondary battery stand for 2 hours at this temperature, then charge it to 4.25V at a constant current of 1 / 3C, then charge it to a cut-off current of 0.05C at a constant voltage; let it stand for 5 minutes, discharge it to 2.8V at a constant current of 1 / 3C, let it stand for 5 minutes, and calculate the discharge capacity at this rate;
[0155] (2) High-temperature long cycle performance and high-temperature DCR growth rate test process: set the ambient temperature to 45°C, let the secondary battery stand for 2 h at this temperature, then charge it to 4.25 V at a constant current of 1 / 3C, then charge it to a cutoff current of 0.05C at a constant voltage, let it stand for 5 min, and discharge it to 2.8 V at a constant current of 1 / 3C, let it stand for 5 min;
[0156] Subsequently, the battery was charged at a constant current of 1C to 4.25V, then charged at a constant voltage to a cutoff current of 0.05C, allowed to stand for 5 minutes, discharged at a constant current of 1C to 2.8V, allowed to stand for 5 minutes, and the charge and discharge cycle at 1C rate was repeated 600 times. The discharge capacity at the first 1C rate was taken as the first capacity to calculate the discharge capacity retention rate of the secondary battery after 600 cycles. At the same time, the secondary battery was taken out every 300 cycles and the cyclic DC resistance DCR growth rate was tested after the charge state was adjusted to 50%.
[0157] The parameters of each secondary battery and the above test results are shown in Table 2, where B = g*h / Dv 50 .
[0158] Table 2
[0159]
[0160] From Table 2 we can see that:
[0161] (1) The positive electrode material described in the present application is compounded with polycrystalline nickel cobalt lithium manganese oxide secondary particles and single crystal nickel cobalt lithium manganese oxide particles, and at the same time, the size relationship of the two materials is constructed, which can not only ensure the dense filling effect of single crystal nickel cobalt lithium manganese oxide and polycrystalline nickel cobalt lithium manganese oxide secondary particles, but also make the stress points more dispersed, and can provide support points to alleviate the rupture problem of polycrystalline nickel cobalt lithium manganese oxide particles under high compaction, and the reaction probability with the electrolyte can also be kept at a low level. At the same time, it will not cause the overall material charge transfer impedance, solid phase mass transfer coefficient, etc. to have large differences due to the large difference in particle size, and the depth of lithium insertion and deinsertion is obviously different during the charging and discharging process, thereby affecting the cycle stability and safety. After the positive electrode material is prepared into a secondary battery, the transition metal elements in the material migrate to the negative electrode plate at a low degree after cycling, and the residual concentration does not exceed 1500ppm. The prepared secondary battery has excellent electrochemical performance, and the capacity retention rate after 600 cycles in a high temperature environment can reach more than 85%, and the DCR growth rate can be maintained below 20%.
[0162] (2) It can be seen from Examples 1 to 12 that the polycrystalline nickel cobalt lithium manganese oxide secondary particles and the single crystal nickel cobalt lithium manganese oxide particles in the positive electrode material described in the present application are not limited to the parameter regulation during the preparation of the materials. Different process selections lead to differences in the particle size and coating shell of the obtained materials. However, as long as the size restrictions on the two particles described in the present application are met, they can both exhibit excellent stability and electrochemical activity.
[0163] (3) According to Examples 13 to 14 and Example 17, it can be seen that the two particles in the positive electrode material described in the present application are not limited to a specific doping element or nickel-cobalt-manganese ratio. The prepared positive electrode material has high density and ion / electron conduction efficiency when further prepared into an electrode sheet, and the probability of side reactions with the electrolyte is low, and good electrochemical performance can be exhibited.
[0164] (4) In comparison, although Comparative Examples 1 and 2 also selected two types of nickel cobalt manganese oxide particles for compounding to prepare positive electrode materials, due to improper construction size relationship, they failed to achieve good thermal stability when applied to secondary batteries, and the long cycle performance at high temperature was not ideal, the cycle capacity retention rate was less than 85%, and the DCR growth rate reached a maximum of 37.8%.
[0165] (5) According to Example 1, Examples 15 to 16, and Comparative Examples 2 and 3, it can be seen that the two types of nickel cobalt manganese oxide particles need to be compounded to achieve a good matching effect. When polycrystalline nickel cobalt manganese oxide secondary particles or single crystal nickel cobalt manganese oxide particles are used alone as positive electrode materials, good thermal stability cannot be achieved. The secondary batteries prepared from the positive electrode materials described in Comparative Examples 2 and 3 have a DCR growth rate of more than 35% under high temperature cycling. When the mass ratio of the two particles is preferably in the range of (5:5) to (8:2), the comprehensive electrochemical performance of the secondary battery is better, and the degree of migration of transition metal elements in the positive electrode material to the negative electrode sheet after cycling is lower.
[0166] Finally, it should be noted that the above embodiments are intended to illustrate the technical solution of the present application rather than to limit the scope of protection of the present application. Although the present application has been described in detail with reference to the preferred embodiments, a person of ordinary skill in the art should understand that the technical solution of the present application can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present application.
Claims
1. A positive electrode material, characterized in that: It includes single crystal lithium nickel cobalt manganese oxide particles and polycrystalline lithium nickel cobalt manganese oxide secondary particles; the polycrystalline lithium nickel cobalt manganese oxide secondary particles are formed by agglomerating polycrystalline lithium nickel cobalt manganese oxide primary particles; The positive electrode material satisfies: 90≤(D1 / D2)×(D1 / D3)≤460; Wherein, D1μm is the average particle size of polycrystalline lithium nickel cobalt manganese oxide secondary particles; The D2μm is the average particle size of single crystal lithium nickel cobalt manganese oxide particles; The D3 μm is the average particle size of the polycrystalline lithium nickel cobalt manganese oxide primary particles.
2. The positive electrode material according to claim 1, characterized in that The polycrystalline lithium nickel cobalt manganese oxide secondary particle chemical formula includes Li d Ni a Co b Mn c M y O2, wherein M includes at least one of Zr, Sr, Ta, Sb, Y, Nb, Mo, and W, wherein 0.85<a<0.95, 0<b<1, a+b<1, 0.95≤d≤1.1, 0≤y≤0.1, And / or, the chemical formula of the single crystal lithium nickel cobalt manganese oxide particles includes Li d′ Ni a′ Co b′ Mn c′ M′ y′ O2, wherein M′ includes at least one of Zr, Al, Mg, K, Na, Zn, Ge, and Ba, wherein 0.87<a′<0.96, 0<b′<1, a′+b′<1 and 0.95≤d′≤1.1, 0≤y′≤0.
1.
3. The positive electrode material according to claim 2, characterized in that The positive electrode material satisfies at least one of the following conditions: (1) 8μm≤D1μm≤16μm; (2) 3μm≤D2μm≤6μm; (3) 0.1μm≤D3μm≤0.3μm; (4)a≤a′.
4. The positive electrode material according to claim 1, characterized in that The particle size distribution curve of the positive electrode material is a double-peak structure curve, and the particle size distribution curve includes a first curve peak and a second curve peak; the peak value of the first curve peak is lower than the peak value of the second curve peak; The particle size distribution curve satisfies: 15≤f / e≤95; The e is the percentage value of the area of the first curve peak to the total area of the particle size distribution curve, and the f is the percentage value of the area of the second curve peak to the total area of the particle size distribution curve.
5. The positive electrode material according to claim 1, characterized in that At least a portion of the surface of the single crystal lithium nickel cobalt manganese oxide particles and the polycrystalline lithium nickel cobalt manganese oxide secondary particles is also provided with a shell layer.
6. The positive electrode material according to claim 5, characterized in that The shell layer comprises an oxide of element X, wherein X comprises at least one of Mg, Zn, Al, Ce, Ti, Zr, B, and W.
7. The positive electrode material according to claim 6, characterized in that The mass content of the element X in the positive electrode material is 0.02-1%.
8. A secondary battery, characterized in that: It comprises a positive electrode sheet, a negative electrode sheet and an electrolyte, wherein the positive electrode sheet comprises the positive electrode material according to any one of claims 1 to 6, and the electrolyte comprises a fluorine-containing additive; The secondary battery satisfies: 12≤g*h / Dv 50 ≤225; Among them, Dv 50 μm is the particle size when the cumulative volume reaches 50% in the volume distribution of the positive electrode material; The h% is the mass content of the fluorine-containing additive in the electrolyte; The gppm is the concentration of the transition metal element in the negative electrode plate after the secondary battery is charged and discharged for 600 times. The temperature of the charge and discharge cycle is 45°C, the charge and discharge rate is 1C / 1C, and the charge and discharge cut-off voltage is 2.8V to 4.25V.
9. The secondary battery according to claim 8, characterized in that: The secondary battery satisfies at least one of the following conditions: (1)6μm≤Dv 50 μm≤15μm; (2)0.1%≤h%≤3%; (3)150ppm≤gppm≤1500ppm.
10. An electrical device, characterized in that: The invention comprises the secondary battery according to any one of claims 8 to 9, wherein the secondary battery is used as a power supply for the electrical device.
Citation Information
Cited By
Ternary precursor with continuously controllable particle size distribution width, preparation method of ternary precursor, positive electrode material, lithium ion battery and electric equipment
CN121929758A